Obstruction Of Justice By The Mass Against The Arrest Of Drug Syndicate - Gomgom Manurung (UM.Tapanuli Selatan, 2024)
Institution is a government organ that is designated as an institution and is given the authority to carry out its functions based on the Republic of Indonesia Law Number 2 of 2002 concerning the Republic of Indonesia National Police, contained in article (2) which contains the function of the police as one of the functions of the State government in the field of maintaining public security and order, law enforcement, protection, protection, and service to the community , in Indonesia, the government continues to strive to emphasize and reduce the number of crimes that occur, one of which is crimes caused by drug abuse , but in the arrest of narcotics dealers, there are often acts of obstruction of justice by the masses . The research method used is a type of qualitative legal research . The results of the study indicate that police officers can fire warning shots 3 (three) times, as regulated in Protap No.1/V/2001 concerning the Use of Firearms against masses who obstruct/ Obstruction of justice in the arrest of drug dealers .